MENAKAR EFEKTIFITAS PROGRAM CORPORATE SOCIAL RESPONSIBILTY (CSR) PERUSAHAAN - Riyadi - Riyadi (Politeknik Negeri Semarang, 2015)
Up to now, big fund has been allocatedcompany for Coroporate SocialResponsibility-CSR. For example TelkomJateng –DIY at lest Rp 41,3 Billion has beenshared during 2014 for Partnership danEnvironment empowerment (Kemitraan danBina Lingkungan). More Badan Usaha MilikNegara –BUMN and big company inIndonesia are illustrated potential funding tocreate social programs. Big problem to getanswer is how far that social programs hasbeen held able to give benefit for target groupor we can say that is the programimplemented effective for target? CSRprogram has been formulated by companycan be classified such as Education,Research, Developing people's economy andRugged country, Socio Economic MUDIKfree. Based on the four program can beconcluded that Developing people's economyand Rugged country more effective thanother program and also giving Social Welfaresustain and long term